C57BL/6 Mice Pretreated With Alpha-Tocopherol Show a Better Outcome of Trypanosoma cruzi Infection With Less Tissue Inflammation and Fibrosis - Silva, Amanda C. O.; Bonfim, Maiara; Fontes, Jonathan L. M.; dos-Santos, Washington L. C.; Mengel, José; Cardillo, Fabíola (Frontiers in Immunology, 2022)
Chagas disease is accompanied by a multisystem inflammatory disorder that follows Trypanosoma cruzi infection. Alpha-tocopherol has been described as an antioxidant and a potential adjuvant to enhance immune responses to vaccines. Therefore, we have evaluated the immune response to T. cruzi infection upon alpha-tocopherol pre-administration. The results show that administration of alpha-tocopherol before the infection results in lower parasitemia and lower mortality of C57BL/6 mice infected with the Tulahuen T. cruzi strain. Alpha-tocopherol administration in normal C57BL/6 mice resulted in higher levels of IFN-γ production by T and NK cells before and after the infection with T. cruzi. More importantly, previous administration of alpha-tocopherol increased the production of IL-10 by T and myeloid suppressor cells and the formation of effector memory T cells while decreasing the expression of PD-1 on T cells. These results suggest that alpha-tocopherol may limit the appearance of dysfunctional T cells during the acute and early chronic phases of T. cruzi infection, contributing to control infection. In addition, alpha-tocopherol could diminish tissue inflammation and fibrosis in late acute disease. These results strongly suggest that alpha-tocopherol may be a helpful agent to be considered in Chagas disease.